ANALISIS PENGUKURAN LEARNING ORGANIZATION DAN LANGKAH STRATEGIS PENINGKATANNYA PROGRAM STUDI STRATA SATU FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS BENGKULU - , JUSTINA KERIAHEN S.E, Dr. Ir. R. Wahyu Supartono ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was aimed to measure learning organization for three studies program : [1] Economy of Development, [2] Economy of Management, [3] and Economy of Accountancy which were parts of higher education of Universitas Bengkulu